ANALISIS MINAT BELI KONSUMEN SEPATU REEBOK - Muhammad Kevyn Reza Pahlevi (2020)
ANALYSIS OF INTEREST BUY REEBOK SHOES By Muhammad Kevyn Reza Pahlevi ABSTRACT This study aims to analyze and prove Promotion, Brand Image, and Prices for Interest in Buying Reebok shoes. This research method uses quantitative descriptive with user population of sport shoes with 100 respondents. Data collection is done through a questionnaire with non-probability sampling methods, especially purposive sampling and testing this hypothesis using regression analysis probability level 5% (0.05). Data analysis techniques using Smart PLS 3.3.2. The results of this study indicate that (1) Promotion has a significant effect on Purchase Interest, (2) Brand Image has a significant effect on Purchaes Interset, and (3) Price have a significant effect on Purchase Interest. Keywords: Promotion, Brand Image, Price, Purchase Interest